Critical load cases for lattice transmission line structures subjected to downbursts: Economic implications for design of transmission lines. (15th March 2018) - El Damatty, Ashraf; Elawady, Amal
Highlights: The effect of the downburst loads on the response of transmission line systems. A parametric study is conducted accounting for the possible loading scenarios on different power line systems. Downburst critical load profiles that cause maximum internal forces in the studied systems are identified. An economical assessment regarding the inclusion of these wind profiles in the design of the selected power line systems is provided. Abstract: An extensive research program was recently conducted at The University of Western Ontario, Canada to investigate the load profiles that can be used in the analysis and the design of transmission towers subjected to downbursts. This research was motivated by many transmission line failures that have occurred in different locations around the globe during downburst events. It was also triggered by the fact that the existing codes of practice and guidelines provide very limited information regarding the critical load profiles associated with downbursts, which act on the towers and conductors of a transmission line system. One of the challenges in predicting the critical forces acting on the towers and conductors is that they are not only dependent on the magnitude of the event but also on its size and location relative to the center of the tower. This complexity results from the localized nature of such events. In the current study, an extensive parametric study is conducted on a number of transmission line systems to evaluate their critical response to downburst loads. The study considers the variations in the downburst location, angle of attack, and size to determine the effect of changing these parameters on the response of the transmission line systems. Based on the results obtained from this parametric study, three critical load cases are identified. The studied towers are then used to assess the economic impact of applying those load cases, expressed by the increase in the weight of the tower.